The Influence of Free Nutritious Food Program on Students' Learning Motivation At SMPN 1 Sungguminasa, Gowa Regency - Syamsidah, Syamsidah; Qur’ani, Besse; Burhanuddin, Izmi; Amir, Syarah Syam (Indonesian Journal of Social and Educational Studies, 2025)
Abstract. This study aims to analyze the effect of a free nutritious food program on the increase of students’ learning motivation at SMP Negeri 1 Sungguminasa, Gowa Regency. A quantitative approach was employed with a one-group pretest-posttest design. The study sample was 90 randomly selected students. Data were collected through a questionnaire to measure learning motivation before (pre-test) and after (post-test) the program. Descriptive analysis showed a significant increase in learning motivation. The average score of student motivation increased from 2.732 (category "Enough") in the pretest stage to 4.083 (category "High") in the posttest stage. Based on the normality assumption test, the data were not normally distributed, so the hypothesis analysis was continued with the Wilcoxon Signed-Rank test. The test showed an Asymp. Sig. (2-tailed) value of 0.000, which proved that there was a significant difference between student learning motivation before and after the intervention was significantly different. This finding confirms that fulfilling basic nutritional needs is an important foundation to support student academic success and motivation Kata Kunci: Influence; Free Nutritious Food; Learning Motivation; Students